Konsep Simbol Keagamaan Yang Sakral Menurut Mircea Eliade Dan Relevansinya Bagi Umat Kristiani Dalam Relasi Antar Agama Di Indonesia - Bruto, Siprianus; Widyawati, Fransiska; Tangi, Antonius Marius (DIEGESIS: Jurnal Teologi Kharismatika, 2024)
Incidents of religious harassment are frequently reported in Indonesia, often manifesting as insults or damage to sacred religious symbols, including those of Christianity. This not only disrupts the tranquility of the Christian community but also undermines interfaith relationships. This study explores the thoughts of Mircea Eliade on sacred religious symbols, distinguishing them from the profane, and assesses their relevance to Christians and the development of interfaith relations. The research aims to reinforce Christian understanding of the sacred and profane within their religion and to correlate these concepts with biblical principles. A qualitative approach, specifically a literature review, is employed in this study. The findings suggest that Eliade’s philosophy provides a theoretical framework for comprehending the sanctity of symbols across religions. Each religion has its unique interpretation of the sacred and profane, shaped by its theological and historical context. Sacred elements demand a different level of respect and protection compared to the profane. Eliade’s philosophy aligns with the interpretation of the Scriptures, which also employ symbols to depict the presence of the Holy Trinity. For Indonesian Christians, Eliade’s thoughts are relevant as they encourage religious communities to respect each other’s religious symbols, engage in symbolic dialogues, and strengthen faith experiences and relationships. Eliade’s philosophy can enrich Christians’ understanding of the sanctity of religious symbols. Externally, Christians can apply Eliade’s philosophy to foster respect and build tolerant and inclusive interfaith relationships. Keywords: Mircea Eliade; Symbol; Sacred; Religious Relations; InfidelAbstrak Insiden pelecehan agama sering dilaporkan di Indonesia, seringkali berwujud penghinaan atau kerusakan terhadap simbol-simbol sakral agama, termasuk simbol-simbol milik agama Kristen. Hal ini tidak hanya mengganggu ketenangan komunitas Kristen tetapi juga merusak hubungan antaragama. Studi ini mengeksplorasi pemikiran Mircea Eliade tentang simbol-simbol keagamaan yang sakral, membedakannya dari yang profan, dan menilai relevansinya bagi umat Kristen dan pengembangan hubungan antaragama. Penelitian ini bertujuan untuk memperkuat pemahaman umat Kristen tentang konsep sakral dan profan dalam agama mereka dan untuk mengaitkan konsep-konsep ini dengan prinsip-prinsip Alkitab. Pendekatan kualitatif, khususnya studi literatur, digunakan dalam penelitian ini. Temuan menunjukkan bahwa filsafat Eliade memberikan kerangka teoritis untuk memahami kesucian simbol di berbagai agama. Setiap agama memiliki interpretasi unik tentang sakral dan profan, yang dibentuk oleh teologi dan konteks historisnya. Elemen-elemen sakral menuntut tingkat penghormatan dan perlindungan yang berbeda dibandingkan dengan yang profan. Filsafat Eliade sejalan dengan interpretasi Kitab Suci, yang juga menggunakan simbol untuk menggambarkan kehadiran Allah Tritunggal. Bagi umat Kristen di Indonesia, pemikiran Eliade relevan karena mendorong komunitas agama untuk saling menghormati simbol-simbol agama masing-masing, melakukan dialog simbolik, dan memperkuat pengalaman dan hubungan iman. Pemikiran Eliade dapat memperkaya pemahaman umat Kristen tentang kesucian simbol-simbol keagamaan. Secara eksternal, umat Kristen dapat menerapkan pemikiran Eliade untuk menunjukkan penghormatan dan membangun hubungan antaragama yang toleran dan inklusif.Kata Kunci: Mircea Eliade; simbol; sakral; relasi agama; kafir